The Use of Urdu Loanwords in American English During the 1979 Soviet-Afghan Intervention: A Corpus-Based Analysis - Mumtaz Yaqub (JELLL, 2025)
This study examines the presence and frequency of Urdu loanwords in American English during the 1979 Soviet intervention in Afghanistan. Using the Time Magazine corpus available through COCA and a composed list of 278 Urdu words from the Collins American English Dictionary, the research analyzes how geopolitical events influence lexical borrowing in media discourse. Findings show that political, religious, and cultural terms—particularly mujahideen, Taliban, imam, and Shia—experienced marked increases in frequency during 1979. These patterns suggest that media outlets adopt culturally embedded terminology to ensure accuracy and contextual depth during foreign conflict reporting. The study contributes to contact linguistics by demonstrating that geopolitical crises can accelerate lexical borrowing and shape patterns of lexical integration in American English.